A three‐genome five‐gene comprehensive phylogeny of the bulbous genus Narcissus (Amaryllidaceae) challenges current classifications and reveals multiple hybridization events. Issue 4 (4th August 2017) - Marques, Isabel; Fuertes Aguilar, Javier; Martins-Louçao, Maria Amélia; Moharrek, Farideh; Nieto Feliner, Gonzalo
Abstract: Besides being one of the most popular ornamental bulbs in western horticulture, the Mediterranean genus Narcissus has been the subject of numerous studies focusing on a wide scope of topics, including cytogenetics, hybridization and the evolution of polymorphic sexual systems. Phylogenetic hypotheses based on chloroplast data have provided a backbone for the genus but a detailed phylogenetic framework is still lacking. To fill this gap, we present a phylogenetic study of the genus using five markers from three genomes: ndhF and matK (chloroplast DNA), cob and atpA (mitochondrial DNA), and ITS (nuclear ribosomal DNA). In addition, we use chromosome counts from 89 populations representing 69 taxa. All analyses confirm that Narcissus is monophyletic with two main lineages largely corresponding to subg. Hermione and subg. Narcissus, but with incongruences between organellar and nuclear ribosomal phylogenies. At the infrageneric levels, our phylogenetic results challenge well‐established taxonomic groups, such as sect. Jonquillae, sect. Bulbocodii and sect. Pseudonarcissi, each of which contains at least two distinct lineages that do not constitute monophyletic groups, and highlight the influence of allopolyploid species in the monophyly of sections within subg. Hermione. The type of the genus and its section is also nested within sect. Pseudonarcissi supporting new nomenclatural changes. Our results also confirm the intersubgeneric hybrid nature of several hybrids including allopolyploids (e.g., N. dubius, N. tortifolius, N. miniatus). Morphological and cytogenetic evidence independently support the hypothesis that some of the incongruence can be attributed to hybridization, such as the splits of sect. Bulbocodii and sect. Pseudonarcissi or the disparate phylogenetic placements of sect. Aurelia and sect. Ganymedes. Together, this indicates a significant role for reticulate evolution in shaping the diversity of this genus. A Bayesian divergence time analysis suggests that the major diversification events took place during the Neogene and provides younger estimates for the main nodes than previous studies, which fit paleoclimatic and paleotectonic reconstructions of the western Mediterranean during this period.